BENTUK DAN FUNGSI TUTURAN EKSPRESIF DALAM BAHASA PRANCIS - Perdi Rahayu, Siti (LITERA, 2013)
This study aims to describe forms, meanings, and functions of expressive utterances in French. The data were collected through listening and note-taking. The forms were analyzed by means of a substitution method and the functions by means of a referential correspondence method. The results are as follows. First, the forms and meanings of expressive utterances include (a) literal direct speech acts, (b) literal indirect speech acts, (c) non-literal direct speech acts, and (d) non-literal indirect speech acts. Second, the functions of expressive utterances include (a) congratulating, (b) thanking, (c) expressing sympathy/condolences, (d) complimenting, (e) apologizing, (f) criticizing, (g) complaining, and (h) blaming.